Evolution: Oxygen and early animals - Rytkönen, Kalle T (eLife, 2018)
The biology of sponges provides clues about how early animals may have dealt with low levels of oxygen.
Keywords: hypoxia-inducible factor; Tethya wilhelma; oxygen sensing; early animal evolution; Porifera; Ctenophora